Moderators of ayahuasca’s biological antidepressant action - Sousa, Geovan Menezes de; de Oliveira Tavares, Vagner Deuel; de Menezes Galvão, Ana Cecília; de Almeida, Raíssa Nóbrega; Palhano-Fontes, Fernanda; Lobão-Soares, Bruno; de Morais Freire, Fúlvio Aurélio; Nunes, Emerson Arcoverde; Maia-de-Oliveira, João Paulo; Perkins, Daniel; Sarris, Jerome; de Araujo, Dráulio Barros; et al. (Frontiers in Psychiatry, 2022)
Introduction The understanding of biological responses to psychedelics with antidepressant potential is imperative. Here we report how a set of acute parameters, namely emotional (depressive symptoms), cognitive (psychedelic experience), and physiological (salivary cortisol), recorded during an ayahuasca dosing session, modulated serum brain-derived neurotrophic factor (BDNF), serum cortisol (SC), serum interleukin 6 (IL-6), plasma C-reactive protein (CRP), and salivary cortisol awakening response (CAR). Methods Results were analyzed 2 days after the psychedelic intervention (ayahuasca) versus placebo in both patients with treatment-resistant depression and healthy volunteers. These measures were assessed as part of a randomized double-blinded, placebo-controlled trial (n = 72). Results Results revealed that larger reductions of depressive symptoms during the dosing session significantly moderated higher levels of SC in patients. Whereas lesser changes in salivary cortisol levels during the ayahuasca intervention were related to higher BDNF levels in patients with a larger clinical response in the reduction in depressive symptoms. No moderator was found for patient’s CAR, IL-6, and CRP responses to ayahuasca and for all biomarker responses to ayahuasca in healthy controls and in the placebo group. Discussion In summary, some specific emotional and physiological parameters during experimental ayahuasca session were revealed as critical moderators of the improvement of major depression biomarkers, mainly BDNF and SC two days after ayahuasca intake. These findings contribute to paving the way for future studies investigating the biological antidepressant response to psychedelic therapy.